Incidence and Histopathology of Sebaceous Gland Tumors in Dogs - Patel, MP; Ghodasara, DJ; Jani, PB; Joshi, BP; Dave, CJ (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The study was aimed to know the prevalence of sebaceous gland tumor in canine and its classification based on histopathology. A total of 569 biopsy samples of canines suspected for neoplastic growth received by Department of Veterinary Pathology from TVCC departments of College of Veterinary Science and A.H. Anand over last 16 years (2001 to 2017) were analyzed. The biopsy samples were subjected to histopathological examinations by using H & E staining. Out of 569 biopsy samples, sebaceous gland growth was observed in 23 (4.04%) cases. The highest incidence (39.13%) was recorded for 9 to 12 years of age. The incidence of sebaceous gland tumor was observed in all the breeds; however, the Labrador retriever was the most affected breed followed by Pomeranian, non-descript and others. The frequent site for sebaceous gland tumor was eyelid. Out of 23 sebaceous gland tumors, one hyperplasia, 19 adenomas, two , and one adenocarcinoma were observed, suggesting that sebaceous gland adenoma was the most common type of sebaceous gland tumors in canine.